Pelatihan Teknologi PHT pada Usaha Tani Cabai Merah di Desa Dukuh Dempok, Kabupaten Jember - Eliyatiningsih Eliyatiningsih; Iqbal Erdiansyah; Sekar Utami Putri; Dany Hisbullah Al Huda; Ramadhana Putra Pratama (Institut Pertanian Bogor, 2021)
Dukuh Dempok Village is one of the centers of red chili pepper production in Jember District. The problem faced by farmers is the presence of pest attacks.The pests that attack include whitefly (Bemisia tabaci), thrips, anthracnose and fusarium wilt. The purpose of this community service program is to provide education and training related to integrated pest control (IPM) in red chili cultivation. The training includes the multiplication of biological agents Beauveria bassiana and biofertilizer Trichoderma, as well as planting of refugia flowers around the red chili plantations. The training was conducted using the plot demonstration method. From the results of extension activities, data on farmers' knowledge improvement related to IPM control were obtained. The average pre-test score before the activity was 41.5 and the average post-test score of farmers after the activity was 87. After the training, the partner farmers were also able to multiply biological agents and make biological fertilizers and apply them to red chili cultivation. From the evaluation results, it is known that the application of B. bassiana, planting of refugia flowers, and the application of Trichoderma sp or the Beart method can reduce the use of pesticides by up to 50%. From these activities, farmers get new knowledge and technology related to red chili cultivation which is useful for increasing production, reducing pesticide use, reducing production costs, and obtaining maximum profits.